Draft Annual Plan, 2003-2004 A Supplement of Volume II Statement III Schemewise Outlays and Expenditure Government of Uttar Pradesh - Planning Commission (Planning Commission, 2003)
Agriculture and Allied Activities, Rural Development, Special Area Programmes, Irrigation and Flood Control, Energy, Industry and Minerals, Transport, Communication (No Programme in State Plan), Science, Technology and Environment, General Economic Services, Education, Medical and Public Health, Water Supply, Sanitation, Housing and Urban Development, Information and Publicity, Welfare of SC/ST and Other Backward Classes, Labour and Employment, Social Security and Welfare and Nutrition, General Services.
Government of Uttar Pradesh, State Planning Commission